Comparing Titania‐Based Architectures for Perovskite Solar Cells: A Combined Optical–Electronic Loss Analysis. Issue 1 (29th November 2017) - Kovalsky, Anton; McCleese, Christopher; Lin, Wei‐Chun; Goldberg, Seth; Kolodziej, Charles; Burda, Clemens
Abstract: Combined optical and electronic loss analysis is applied in comparing MAPbI3 and MAPbI3− x Cl x as light absorbers in both planar and mesoporous TiO2 absorber scaffolds in order to determine the specific effects of these architectural variations on energy‐dependent loss mechanisms in perovskite‐sensitized solar cells. A transfer matrix model is used to separate electronic losses from optical losses in the form of parasitic absorption. It is reported that MAPbI3− x Cl x is the superior absorber due to increased crystallinity, but that the benefit from using the chloride‐assisted formulation is negated when the absorber is deposited on a mesoporous substrate. It is also reported that some beneficial electronic and optical effects are associated with the mesoporous TiO2 : decreased parasitic absorption at short wavelengths and possible enhancement of charge transfer; the overall use of the mesoporous scaffold typically seen in dye‐sensitized solar cells is not appropriate for perovskite‐sensitized solar cells, where it disrupts the formation of large perovskite grains. The analysis also provides important insight into the application of transfer matrix modeling in pseudoplanar systems such as the ubiquitous mesoporous solar cell architecture. Abstract : Combined optical and electronic loss analysis is a comprehensive solar cell characterization strategy that provides qualitative and quantitative insight into the efficiency‐leeching processes in photovoltaic devices. By tracking the progression of the photoconversion pathway from light absorption to photocurrent extraction, this methodology elucidates the relationship between the design and performance of perovskite‐based solar cells of different architectures.